2016
DOI: 10.1039/c6ra01627h
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics study of the Al–water reaction promoted by an ultrasonically prepared Al(OH)3 suspension

Abstract: The hydrogen-generation rate of Al in a Al(OH)3 suspension is comparable to the behavior of Al in a NaOH solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…After removal of the alumina film, the Al–H 2 O reaction starts and a core‐shell structure formed. The exterior consists of a hydration layer that contains Al(OH) 3 /Al(OH) 4 − , and the interior consists of metallic Al . The fresh hydration layer on the Al surface has a relatively large specific amorphous and porous surface area (Figure C), which facilitates OH − and H 2 O transport and increases the concentration at the interface of Al/Al(OH) 3 /Al(OH) 4 − , resulting in Al corrosion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of the alumina film, the Al–H 2 O reaction starts and a core‐shell structure formed. The exterior consists of a hydration layer that contains Al(OH) 3 /Al(OH) 4 − , and the interior consists of metallic Al . The fresh hydration layer on the Al surface has a relatively large specific amorphous and porous surface area (Figure C), which facilitates OH − and H 2 O transport and increases the concentration at the interface of Al/Al(OH) 3 /Al(OH) 4 − , resulting in Al corrosion.…”
Section: Resultsmentioning
confidence: 99%
“…And the dissolution of Al(OH) 3 the interior consists of metallic Al. 23 The fresh hydration layer on the Al surface has a relatively large specific amorphous and porous surface area ( Figure 5C), which facilitates OH − and H 2 O transport 24,25 and increases the concentration at the interface of Al/Al(OH) 3 /Al(OH) 4 − , resulting in Al corrosion.…”
Section: Al-h 2 O Reaction Dynamics In Different Mediamentioning
confidence: 99%
“…Some active metals can be used to produce hydrogen by their chemical reactions with an aqueous solution; among these, aluminium is preferred because of its low cost, abundant reserves and environment-friendliness. 3,4 However, since aluminium is easily oxidized, it is difficult for pure aluminium to react with water continually. Therefore, the key for hydrogen generation from aluminium is to remove the thin layer of oxides from aluminium.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al have demonstrated the mechanism and influence factors for the generation of hydrogen from an Al/water system. They proposed that hydroxide and oxides could dissociate water molecules and promote the hydration of the passive oxide film on the surface of Al particles .…”
Section: Introductionmentioning
confidence: 99%
“…The reclaims of Al metals from the reaction waste, Al(OH) 3 , can be done by a low temperature (<100°C) chemically reduction method in ionic liquids, making Al/water an excellent system for the clean energy. 18 Deng et al [19][20][21][22][23] have demonstrated the mechanism and influence factors for the generation of hydrogen from an Al/water system. They proposed that hydroxide and oxides could dissociate water molecules and promote the hydration of the passive oxide film on the surface of Al particles.…”
Section: Introductionmentioning
confidence: 99%